The importance of using the heritage of our Great Scientists in lifelong education and preparing students for family life (Multidisciplinary Journal of Science and Technology, 2024)
The article talks about the importance of using the creative heritage of our scientists in organizing the educational process of students and preparing them for life, developing in them the positive qualities of the concept of family.